Pentraxin 3 in Cardiovascular Disease - Ristagno, Giuseppe; Fumagalli, Francesca; Bottazzi, Barbara; Mantovani, Alberto; Olivari, Davide; Novelli, Deborah; Latini, Roberto (Frontiers in Immunology, 2019)
The long pentraxin PTX3 is a member of the pentraxin family locally produced by stromal and myeloid cells in response to proinflammatory signals and microbial moieties. Prototype of the pentraxin family is C reactive protein (CRP), a widely-used biomarker in human pathologies with an inflammatory or infectious origin. Data available so far describe PTX3 as a multifunctional protein acting as functional ancestor of antibodies and playing a regulatory role in inflammation. Cardiovascular disease (CVD) is a leading cause of mortality world while, and inflammation plays a crucial role in promoting CVD. Data obtained in animal models indicate that PTX3 can exert cardioprotective and atheroprotective roles regulating inflammation. PTX3 has been investigated in several clinical settings as possible biomarker of cardiovascular diseases. Data collected so far indicate that PTX3 plasma levels are rapidly increased in acute myocardial infarction, heart failure and cardiac arrest, reflecting the extent of tissue damage and predicting the risk of mortality.